Pedagogical Interactions Based on the Local Wisdom of Kampung Adat Dukuh for Strengthening Students' Mutual Cooperation and Religious Character - Hikmat Hikmat; Yadi Ruyadi; Juntika Nurhihsan; Encep Syarief Nurdin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study examines how local wisdom shapes pedagogical interactions and character formation among elementary school students in Kampung Adat Dukuh amid ongoing digital transformation. While previous research has emphasized cultural values, the mechanisms through which these values are transmitted in indigenous communities remain underexplored. Using a qualitative approach with an educational ethnography design, this study focuses on six students in Grades IV–VI as primary participants, supported by interviews with customary leaders, religious figures, community leaders, village officials, and parents. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using an interactive model. The findings show that pedagogical interactions are embedded in communal activities such as gotong royong (mutual cooperation), religious gatherings, congregational prayers, and other shared social practices involving both children and adults. Values are internalized through active participation, habituation, role modeling, and intergenerational engagement. These processes indicate that character education occurs naturally within everyday community life rather than through formal instruction. The study introduces the concept of a “living pedagogy system,” referring to a continuous, socially embedded learning process rooted in community practices. It highlights indigenous communities as dynamic pedagogical ecologies that remain relevant for strengthening children’s character in the face of digital-era challenges.